Explainable, transparent autonomous agents and multi-agent systems : first International Workshop, EXTRAAMAS 2019, Montreal, QC, Canada, May 13-14, 2019, Revised selected papers /: first International Workshop, EXTRAAMAS 2019, Montreal, QC, Canada, May 13-14, 2019, Revised selected papers. (2019) - Unknown
No abstract available